Psychometric properties of the Epworth Sleepiness Scale in Brazilian medical students - Silva, Renato Canevari Dutra da; Garcez, Anderson; Brugnoli, Adriana Vieira Macedo; Pattussi, Marcos Pascoal; Olinto, Maria Teresa Anselmo (Arquivos de Neuro-Psiquiatria, 2025)
Background Excessive daytime sleepiness (EDS) refers to the propensity to become drowsy or fall asleep when the intention and expectation would be to stay awake, and the Epworth Sleepiness Scale (ESS) is an easy-to-apply instrument that can be used to assess the presence of EDS.Objective To evaluate the psychometric properties of the ESS, including its construct validity and internal consistency, in a population of university students.Methods Two samples of 400 students from the medicine program of a university located in the Midwest of Brazil were randomly selected from a cross-sectional academic study conducted in 2018. Construct validity was examined through exploratory and confirmatory factor analysis of the eight items of the ESS, and the internal consistency was evaluated using the Cronbach's α coefficient (α).Results It was found that factor analyses revealed better adjustment measures when considering the ESS to be two-dimensional, grouped into two main factors: the first factor referring to the evaluation of sleepiness at rest, and the second referring to drowsiness in activity (standardized root mean square residual [SRMR] = 0.053; root mean square error of approximation [RMSEA] = 0.095; Comparative Fit Index [CFI] = 0.937; and Tucker-Lewis Index [TLI] = 0.908; p < 0.05). Moreover, the ESS presented an adequate internal consistency (α = 0.75).Conclusion The present study showed general psychometric properties adequate for the ESS in medical students, including an acceptable construct validity and internal consistency. Thus, the ESS may be suitable to assess EDS in university students, especially medical students.
Keywords: Disorders of Excessive Somnolence; Sleepiness; Epworth Sleepiness Scale; Students, Medical